LAW PROTECTION OF OUTSOURCING WORKERS IN EMPLOYMENT LAW POST THE JOB CREATION PERPU - Agus, Dede; PM, Hilton Tarnama (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to describe how the law position of outsourced workers and the law protection of outsourced workers post the law No.2 of 2022 on Job Creation. The use of outsourcing workers has a strategic position for employers in the unconducive business. But not strategic position for law protection of workers, because the impact of outsourcing is very unlack to workers. Therefore, law protection is needed for outsourcing workers to realize social justice in the employment. This research method, normative juridical based on secondary data and descriptive analysis of qualitative. The results showed that the law position of outsourcing workers in agreement of work with the company contracting and the outsourcing worker on the provision of worker services has a working relationship with the service provider company not to the user/employer. The law protection of outsourced workers post the law No.2 of 2022 on Job Creation has protected outsourcing workers. Because the law No.2 of 2022 on Job Creation have two models agreement of work, such as: PKWTT or PKWT with TUPE